2000
DOI: 10.1038/81642
|View full text |Cite
|
Sign up to set email alerts
|

Mutant WD-repeat protein in triple-A syndrome

Abstract: Triple-A syndrome (MIM 231550; also known as Allgrove syndrome) is an autosomal recessive disorder characterized by adrenocorticotropin hormone (ACTH)-resistant adrenal insufficiency, achalasia of the oesophageal cardia and alacrima. Whereas several lines of evidence indicate that triple-A syndrome results from the abnormal development of the autonomic nervous system, late-onset progressive neurological symptoms (including cerebellar ataxia, peripheral neuropathy and mild dementia) suggest that the central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
233
1
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(244 citation statements)
references
References 20 publications
5
233
1
5
Order By: Relevance
“…Several of the mutations identified in triple A patients result in truncation of the C terminus of ALADIN, suggesting that the C-terminal domain is important for the function of ALADIN (3,4,(7)(8)(9)(10). We analyzed the subcellular localization of the shortest pathogenic C-terminal truncation of ALADIN, the nonsense mutation R478X, which lacks the C-terminal 69 aa and terminates after glycine 477.…”
Section: The C-terminal Domain Of Aladin Is Essential For Npc Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of the mutations identified in triple A patients result in truncation of the C terminus of ALADIN, suggesting that the C-terminal domain is important for the function of ALADIN (3,4,(7)(8)(9)(10). We analyzed the subcellular localization of the shortest pathogenic C-terminal truncation of ALADIN, the nonsense mutation R478X, which lacks the C-terminal 69 aa and terminates after glycine 477.…”
Section: The C-terminal Domain Of Aladin Is Essential For Npc Targetingmentioning
confidence: 99%
“…Sequencing of the ALADIN gene from several triple A patients has identified a variety of mutations scattered throughout the gene (3,4,(6)(7)(8)(9)(10). A large number of these mutations are nonsense, frameshift, or splice-site mutations that are predicted to truncate the C terminus of ALADIN, suggesting that this domain is important for the function of ALADIN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Triple A syndrome is caused by mutations in the AAAS gene on chromosome 12q13. 2,3 AAAS is ubiquitously expressed with an enhanced expression in the pituitary gland, the gastrointestinal tract and the adrenal gland, tissues that are mostly affected in triple A syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…AAAS is ubiquitously expressed in all tissues tested (Tullio-Pelet et al, 2000), but the expression of ALADIN is not reported until now.…”
Section: Introductionmentioning
confidence: 99%